Cancer Biomarkers Discovery of Methylation Modification With Direct High-Throughput Nanopore Sequencing - Zhang, Junjie; Xie, Shuilian; Xu, Jingxiang; Liu, Hui; Wan, Shaogui (Frontiers in Genetics, 2021)
Cancer is a complex disease, driven by a combination of genetic and epigenetic alterations. DNA and RNA methylation modifications are the most common epigenetic events that play critical roles in cancer development and progression. Bisulfite converted sequencing is a widely used technique to detect base modifications in DNA methylation, but its main drawbacks lie in DNA degradation, lack of specificity, or short reads with low sequence diversity. The nanopore sequencing technology can directly detect base modifications in native DNA as well as RNA without harsh chemical treatment, compared to bisulfite sequencing. Furthermore, CRISPR/Cas9-targeted enrichment nanopore sequencing techniques are straightforward and cost-effective when targeting genomic regions are of interest. In this review, we mainly focus on DNA and RNA methylation modification detection in cancer with the current nanopore sequencing approaches. We also present the respective strengths, weaknesses of nanopore sequencing techniques, and their future translational applications in identification of epigenetic biomarkers for cancer detection and prognosis.